Inclusive teacher: professional practices based on the interpretation of diversity, utopia or realities = Nauczyciel inkluzywny: praktyka zawodowa oparta na interpretacji różnorodności, utopii czy realiów? - Kohout-Diaz, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
What does the notion of inclusive teacher?s identity imply? If he is destined to become an interpreter of diversity, he is called to subjectively assume the singularity of his analysis, appropriate to the consideration of the unforeseen and the variety of the speci?c courses. The subjective identity of the teacher does not become confused with the typical hypertrophied "ego" of our contemporary digital age, nor with a communitarian "we" that tends to swallow the social link to a con?ictual "us or them", nor with a scientistic "it" that excludes the subject.
Keywords: teachers; professionalism; inclusive education; diversity; nauczyciele; profesjonalizm; edukacja włączająca; różnorodność